2009
DOI: 10.1002/pssc.200881224
|View full text |Cite
|
Sign up to set email alerts
|

Group III element substitution effects on Eu‐doped thiogallate phosphors

Abstract: Photoluminescence properties of II‐III2S4:Eu (II=Ca, Sr, Ba; III=Ga, In, Y, La; Eu concentration was 1 mol%) have been investigated systematically. In Ga compounds, well‐known green∼yellow emissions are observed, while the emissions become very weak in In substituted compounds. In III=Y or La compounds, when II=Ca or Sr, red∼infrared emissons which seem to be due to phonon‐terminated transition of the Eu2+ ions are observed, while when II=Ba, strong sharp lines due to the Eu3+ions are detected. These spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Similarly, the lattice parameters of EuGa 2 S 4 are a = 2.0716 nm, b = 2.0404 nm, c = 1.2200 nm 28 . The Eu 2+ ions are expected to occupy the Ca 2+ site in the (Ca 1‐ x Eu x )Ga 2 S 4 phosphors because the ionic radius of Eu 2+ (0.125 nm) differs only slightly from that of Ca 2+ (0.112 nm) when both ions are in eightfold coordination 29 . The Rietveld‐refined cell parameters of the Ca 0.9 Ga 2 S 4 :0.1Eu phosphor investigated in the present work are a = 2.0136 nm, b = 2.0056 nm, c = 1.2109 nm in orthorhombic geometry with D 2h 24 ‐ Fddd symmetry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the lattice parameters of EuGa 2 S 4 are a = 2.0716 nm, b = 2.0404 nm, c = 1.2200 nm 28 . The Eu 2+ ions are expected to occupy the Ca 2+ site in the (Ca 1‐ x Eu x )Ga 2 S 4 phosphors because the ionic radius of Eu 2+ (0.125 nm) differs only slightly from that of Ca 2+ (0.112 nm) when both ions are in eightfold coordination 29 . The Rietveld‐refined cell parameters of the Ca 0.9 Ga 2 S 4 :0.1Eu phosphor investigated in the present work are a = 2.0136 nm, b = 2.0056 nm, c = 1.2109 nm in orthorhombic geometry with D 2h 24 ‐ Fddd symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…28 The Eu 2+ ions are expected to occupy the Ca 2+ site in the (Ca 1-x Eu x )Ga 2 S 4 phosphors because the ionic radius of Eu 2+ (0.125 nm) differs only slightly from that of Ca 2+ (0.112 nm) when both ions are in eightfold coordination. 29 Figure 4. This result is attributed to the CL intensities depending on the volume of electrons penetrating the phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…Kato et al . synthesized Eu 2+ ‐doped MY 2 S 4 (M = Ca, Sr, and Ba) phosphors . They found that the calcium or strontium thioyttrate phosphors, when excited at 500 nm, produced red and near‐infrared emissions, respectively.…”
Section: Photophysical Properties Of the Fabricated Leds Using The Opmentioning
confidence: 99%
“…Kato et al synthesized Eu 2+ -doped MY 2 S 4 (M = Ca, Sr, and Ba) phosphors. 10 They found that the calcium or strontium thioyttrate phosphors, when excited at 500 nm, produced red and near-infrared emissions, respectively. In this study, we extended the chemical composition of the green phosphor to (Zn 0.6 Sr 0.3 Mg 0.1 ) 2 Ga 2 M x S 5+3x/2 :Eu 2+ (M = Group 3 trivalent ion) and investigated the incorporation effects of trivalent ions (Sc 3+ , Y 3+ , or La 3+ ) on the luminescence properties.…”
mentioning
confidence: 99%
“…Therefore, Eu 2+ ‐activated thiogallates are likely to be applied in various fields in the future. However, the literature contains only a few studies on the properties of Eu 2+ ‐activated thiogallates 27–34 . In this account, we systematically analyze Eu 2+ ‐activated thiogallates.…”
Section: Introductionmentioning
confidence: 99%